Development and Validation of a Bioanalytical Method for the Determination of Nimodipine Concentration in Plasma of Rats - Samir Hasson Aziz Ramadhan; Khalid Kadhem Al-Kinani (Iraqi Journal of Pharmaceutical Sciences, 2025)
Nimodipine is a calcium channel blocker used for the prevention of cerebral vasospasm after subarachnoid hemorrhage, a type of strokes. Its unique ability to selectively dilate blood vessels in the brain makes it a crucial medication in neurology. Pharmaceutical analysis of nimodipine is important to ensure its safety, efficacy, and quality, and to establish optimal dosage regimens for patients. Hence, a bioanalytical method based on high performance liquid chromatography (HPLC) was developed and validated to determine the concentration of nimodipine in rat’s plasma that has been spiked with the drug. The current method development included the processing of plasma followed by injection into HPLC system with ultraviolet detector. Sample preparation involved utilizing 1-pentanol as an extraction solvent. Chromatographic separation was performed on octadecylsilane (ODS) column using water/methanol as mobile phase. Nifedipine was used as an internal standard (IS). The validation results indicated that the proposed method is specific and linear for nimodipine within the concentration range of 10.0 to 150.0 ng/mL. The accuracy and precision of the method were assessed for both inter-day and intra-day measurements. The results revealed accuracies ranging from 97.00% to 99.66% and 95.12% to 101.28%, respectively. In terms of precision, the values ranged from 1.17% to 3.10% for inter-day measurement and 1.00% to 2.23%, for intra-day measurements. The recovery rates for nimodipine and nifedipine were 95.91% and 86.61%, respectively. Furthermore, the method demonstrated good stability at short-term room temperature (99.44%), long-term freeze temperature (97.80%), and freeze/thaw (97.04%) conditions. Overall, these findings suggest that the method is suitable for use in pre-clinical pharmacokinetic studies involving involving nimodipine-containing drug delivery system.